2021
DOI: 10.3892/ol.2021.12563
|View full text |Cite
|
Sign up to set email alerts
|

The HOTAIR lncRNA: A remarkable oncogenic promoter in human cancer metastasis (Review)

Abstract: Long non-coding RNA (lncRNA) is a new type of non-coding RNA that has an important regulatory influence on several human diseases, including cancer metastasis. HOX antisense intergenic RNA (HOTAIR), a newly discovered lncRNA, has an important effect on tumour proliferation, migration and metastasis. HOTAIR regulates cell proliferation, changes gene expression, and promotes tumour cell invasion and migration. However, its molecular mechanism of action remains unknown. The present review summarizes the molecular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 92 publications
(113 reference statements)
0
14
0
Order By: Relevance
“…Increasing studies have verified that long noncoding RNAs (lncRNAs) play key roles during the development of multiple human cancers [3][4][5]. Studies have reported that IGF2-AS is a biomarker for cancer diagnosis and prognosis, including as a tumor suppressor in breast cancer [6], a promotor of glycolysis and apoptosis of gastric cancer cells via targeting miR-195/CREB1 axis [7], a potential target for colorectal cancer (CRC) treatment [8], as well as the prognosis and metastasis of gastric adenocarcinoma via serving as a ceRNA of miR-503 to regulate SHOX2 9.…”
Section: Introductionmentioning
confidence: 99%
“…Increasing studies have verified that long noncoding RNAs (lncRNAs) play key roles during the development of multiple human cancers [3][4][5]. Studies have reported that IGF2-AS is a biomarker for cancer diagnosis and prognosis, including as a tumor suppressor in breast cancer [6], a promotor of glycolysis and apoptosis of gastric cancer cells via targeting miR-195/CREB1 axis [7], a potential target for colorectal cancer (CRC) treatment [8], as well as the prognosis and metastasis of gastric adenocarcinoma via serving as a ceRNA of miR-503 to regulate SHOX2 9.…”
Section: Introductionmentioning
confidence: 99%
“…40 So, there are much evidence that HOTAIR may be closely related to the pathogenesis of thyroid cancer. Another study by Chen et al, 2021a, 41 reported that the expression level of HOTAIR was notably higher in the thyroid cancer tissues than in the normal tissues and nodular goiter tissues. Also, HOTAIR could be detected in TC patient plasma, whereas there was almost no HOTAIR expression in the plasma of the healthy volunteers.…”
Section: Discussionmentioning
confidence: 96%
“…There are a number of investigations devoted to the aberrant expression of ncRNAs in different diseases and associated with clinical characteristics of patients, which make them potential diagnostic and prognostic biomarkers. For example, low expression of miR-125a-3p correlates with tumor size, metastasis, invasion and poor prognosis in gastric cancer [ 244 ], and circVIM is upregulated in acute myeloid leukemia patients and associated with poor clinical outcome [ 245 ], whereas oncogenic lncRNA HOTAIR is upregulated in many tumors and promotes their progression [ 246 ].…”
Section: Histone Modifications and Ncrnas: From Theory To Praxismentioning
confidence: 99%